Protocol of the TransformUs SecondaryTeachers’ perceptions of the program reach, effectiveness,adoption, implementation and maintenance schools program: a type II hybrid implementation-effectiveness trial to increase adolescents’ physical activity and reduce sedentary time in secondary schools - Harriet Koorts; Anna Timperio; Jo Salmon; David Revalds Lubans; Gavin Abbott; Nicola D Ridgers; Natalie Lander; Ana María Contardo Ayala; Emiliano Mazzoli (BMJ Open)
Introduction Despite the known health and educational benefits of physical activity and the risks of prolonged sedentary behaviour, only one in 10 adolescents globally meet physical activity guidelines, and three-quarters of the school day is spent sitting. TransformUs, an effective and cost-effective whole-of-school programme for promoting primary school children’s physical activity and reducing sedentary behaviour, has been adapted for secondary schools (TransformUs Secondary). The aim of this paper is to describe the protocol for TransformUs Secondary in relation to implementation and scale-up across Australia, and the real-world effectiveness of the intervention on adolescents’ physical activity and sedentary time, as well as sitting time, sleep, well-being and class and school engagement.Methods and analysis A type II hybrid implementation-effectiveness trial will be conducted using a mixed-methods design. For the implementation trial, TransformUs Secondary will be disseminated via key organisations nationally (eg, state departments of education) and available to all Australian secondary schools (n=1453). Implementation outcomes will be evaluated using the RE-AIM framework (reach, adoption, implementation and maintenance). Data will be collected at the school and teacher levels via the TransformUs website (website analytics), descriptive quantitative surveys, text messages to teachers and qualitative interviews with teachers, students and representatives from key organisations. Descriptive statistics will summarise quantitative data, with regression analyses examining the associations between implementation strategies and outcomes. Implementation levels will be classified as low, moderate or high based on the extent of intervention delivery. Qualitative data will be thematically analysed.We will assess effectiveness outcomes in 10 Victorian secondary schools using a pragmatic 1:1 waitlist control design. The target sample is 600 Year 7–10 students (12–16 years). Primary outcomes include adolescents’ physical activity and sedentary time (assessed with accelerometry), and secondary outcomes include health (sleep and well-being), class and school engagement (on-task behaviour assessed via classroom observation and school attendance) and sitting time (assessed with posture monitors). Descriptive analyses will summarise students’ demographics, physical activity, sedentary behaviour and engagement, while mixed models will evaluate intervention effects on these outcomes, adjusted for confounders. Additionally, qualitative data will be thematically analysed using deductive and inductive coding in NVivo.Ethics and dissemination These trials were approved by the Deakin University Human Research Ethics Committee (2021–269) and by the following education authorities: Australian Capital Territory Education Directorate (RES 2317), New South Wales Department of Education (2022253), Northern Territory Department of Education (20865), Victoria Department of Education (2023_004712), Queensland Department of Education (550/27/2585), South Australian Department of Education (2022–0019), Tasmanian Department of Education (2022–25), Western Australian Department of Education (D23/1152724), and Melbourne Archdiocese Catholic Schools (1232). Results from this study will be disseminated through peer-reviewed journal articles, scientific conferences, summary reports to students and schools and stakeholder meetings.Trial registration number Australian Clinical Trials Registration Registry (ACTRN12622000600741).